Eco-efficiency in infrastructure works and its importance in the environmental awareness of rural communities of Marcas in the context of COVID-19 - Cortijo, Cesar (2023)
The construction industry is one of the activities that most dynamize the world economy, through the appropriation of natural resources, so that it transforms them and generates huge amounts of solid waste of various characteristics; this causes negative impacts on the environment. Given this reality and within the context of the COVID-19 pandemic, we identified the determining factors of the implementation of eco-efficiency for solid waste management in a road infrastructure work, transmitted to workers through periodic training and determined its relationship with the level of environmental awareness perceived by the inhabitants of two communities located in its area of influence belonging to the district of Marcas. The method used was hypothetical-deductive. A proposal for a model of eco-efficient community management of solid waste was proposed based on the results obtained that categorize the economic and productive dimension of eco-efficiency, followed by the socio-cultural dimension as influential elements in the environmental awareness perceived by the inhabitants according to their gender, type of population and level of education; it was determined that there are no significant differences in relation to gender, level of education and area of residence for the affective dimension of environmental awareness.